Verbal Abuses In Kidney Donor Reflected In Jody Picoult's Novel My Sister's Keeper (2008): Semiotic Approach - Wulandari, Gresna Ayu (2012)
This research paper elaborates verbal abuses in kidney donor that is reflected in My Sister's Keeper novel, which is analyzed through semiotic approach. The aim of this study is to analyze My Sister's Keeper novel based on the structural elements and the semiotic analysis of the novel. This study focuses on verbal abuse of the major character named Anna Fitzgerald and to analyze each element based on the signifiers and the signifieds. This research is qualitative research. Type of data of the study is text taken from two data source, primary and secondary. The primary data source of this study is My Sister's Keeper novel written by Jody Picoult, this novel was published by Hodder & Stroughton. And the secondary data source is taken from other sources which are related to primary data such as biography of the writer, criticism in relation to the problem and material related to the study taken from books or internet. The outcome of this study shows the following conclusions. Firstly, based on structural analysis, it shows the character and characterization, setting, plot, point of view, style and theme are interrelated each other and forming a unity. Secondly, based on semiotic analysis, it shows the denotative level and connotative level of the novel. The semiotic analysis uses to describe the meaning of the structural elements of the novel based on the signifiers and signifieds. By using the semiotic analysis, the writer finds some verbal abuses occurring to the major character Anna Fitzgerald. That condition makes Anna conclude to sue her mother of her medical emancipation.